Gender Equality on Education Issues in UN Women’s Article: “Leaving No Girl Behind in Education” - Budi Santoso; Dina Muthmainnah; Lishapsari Prihatini; Siti Lady Havivi; Rahman Hakim (International Journal Labs, 2025)
Gender equality is a global concern as gender points are listed in Sustainable Development Goal (SDG). UN Women is a UN organization dedicated to gender equality and women's empowerment. Their activities collaborate closely with social media to advance women's rights. An article entitled